Shifted Baselines Reduce Willingness to Pay for Conservation - McClenachan, Loren; Matsuura, Ryunosuke; Shah, Payal; Dissanayake, Sahan T. M. (Frontiers in Marine Science, 2018)
A loss of memory of past environmental degradation has resulted in shifted historical baselines, which may result in conservation and restoration goals that are less ambitious than if stakeholders had a full knowledge of ecosystem potential. However, the link between perception of baseline states and support for conservation planning has not been tested empirically. Here, we investigate how perceptions of change in coral reef ecosystems affect stakeholders’ willingness to pay (WTP) for the establishment of protected areas. Coral reefs are experiencing rapid, global change that is observable by the public, and therefore are an ideal ecosystem to test links between beliefs about baseline states and willingness to support conservation. We find that respondents perceived change to coral reef communities across six variables: coral abundance, fish abundance, fish diversity, fish size, sedimentation, and water pollution. Residents who accurately perceived declines in reef health had significantly higher WTP for protected areas (US $256.80 vs. $102.50 per year), suggesting that shifted historical baselines reduce engagement with conservation efforts. If WTP translates to engagement, this suggests that goals for restoration and recovery are likely to be more ambitious if the public is aware of long term change. Therefore, communicating the scope and depth of environmental problems is essential in engaging the public in conservation.